Repeated dribbling ability in young soccer players: Reproducibility and variation by the competitive level - Duarte, J. P.; Tavares, O.; Valente-dos-Santos, J.; Severino, V.; Ahmed, A.; Rebelo-Goncalves, R.; Pereira, J. R.; Vaz, V.; Povoas, S.; Seabra, A.; Cumming, S. P.; Coelho e Silva, M. J. (Journal of Human Kinetics, 2016)
The intermittent nature of match performance in youth soccer supports relevance of ability to repeatedly produce high-intensity actions with short recovery periods. This study was aimed to examine the reproducibility of a repeated dribbling ability protocol and, additionally, to estimate the contribution of concurrent tests to explain inter-individual variability in repeated dribbling output. The total sample comprised 98 players who were assessed as two independent samples: 31 players were assessed twice to examine reliability of the protocol; and 67 juveniles aged 16.1 ± 0.6 years were compared by the competitive level (local, n = 34; national, n = 33) to examine construct validity. All single measurements appeared to be reasonably reliable: total (ICC = 0.924; 95%CI: 0.841 to 0.963); ideal (ICC = 0.913; 95%CI: 0.820 to 0.958); worst (ICC = 0.813; 95%CI: 0.611 to 0.910). In addition, the percentage of the coefficient of variation was below the critical value of 5% for total (%CV = 3.84; TEM = 2.51 s); ideal (%CV = 3.90, TEM = 2.48 s). Comparisons between local and national players suggested magnitude effects as follows: moderate (d-value ranged from 0.63 to 0.89) for all repeated sprint ability scores; large for total (d = 1.87), ideal (d = 1.72), worst (d = 1.28) and moderate for composite scores: the fatigue index (d = 0.69) and the decrement score (d = 0.67). In summary, the dribbling protocol presented reasonable reproducibility properties and output extracted from the protocol seemed to be independent from biological maturation.